Key priorities of physical education and sport sector budgeting laws and regulations in the Russian Federation - Gurinovich, A. G.; Petrova, G. V. (Theory and Practice of Physical Culture, 2019)
The study topic is ranked among the priorities today due to the governmental policies to increase the public financial support for the national physical education and sport sector as required by the national physical education and sport sector development strategies and goals. The article analyzes the basic concepts of the physical education and sport sector budgeting regulations in the context of the valid standards, national policies, national physical education and sport sector development program; federal Life Norm Sports Project; and the newly approved federal budget; and offers a reasonably detailed analysis of an efficient budget disbursement mechanism. On the whole, the article raises the key aspects of the physical education and sport sector budgeting regulations to ensure the physical education and sport sector being designed and managed on a most efficient basis by the relevant legal and regulatory provisions; and to further motivate the regulatory agencies for productive activity to offer a versatile and effective financing system for the sector using the available legal and regulatory mechanisms. It is the first attempt in the national research literature to make a detailed analysis of the issue in the context of the newly approved federal budget.